GAMBARAN KEMANDIRIAN LANJUT USIA ACTIVITY DAILY LIVING DI WILAYAH KERJA PUSKESMAS PEGANDAN KOTA SEMARANG - Ayuningtyas, Nadiah Ratmanasari; Mawarni, Atik; Agushybana, Farid; Nugroho, R. Djoko (Jurnal Kesehatan Masyarakat (e-Journal), 2020)
Life expectancy is getting higher. The increasing number of elderly people can cause various health problems. Elderly who changes physically, mentally, and socially will increase their independence in carrying out daily activities. The aim of this study is to describe the independence of elderly in fulfilling activity daily living. This study uses a quantitative-descriptive method using a cross-sectional study. The population in this study is the elderlies more than 60 years old as many as 3,379 and samples chosen using simple random sampling techniques. The sample is 108 elderlies. The instruments of this study are Katz Index and Lawton Index questionnaires. Univariate data analysis uses frequency distribution. The results showed the age group 60-74 years (79.6%), female (75.9%), married status (52.8%), senior high school (25.0%), unemployed status ( 75.0%), and live with other people (75%). Most of the elderly do their daily activities independently, while the elderly require compilation using the telephone, shopping, doing homework and using transportation or driving. Optimizing the provision of information through counseling about activities daily living, providing IEC (Information, Education, and Communication) and doing interpersonal communication.